From Paperwork to Performance: E-HR’s Impact on Organizational Performance in Saudi Arabia - Samar S. Alharbi (Kurdish Studies, 2024)
Presently, e-HRM practices encompass transactional tasks such as performance management, compensation, training, recruitment, and transformational activities, all of which contribute to organizational performance. This study aims to investigate the impact of e-HR on organizational performance in KSA. Using a deductive and quantitative research approach, data was collected through questionnaires from a sample of 245 individuals selected via simple random sampling. Statistical tools, including descriptive and regression analysis, were utilized for data analysis. The study’s findings demonstrate a positive association between eHR practices and employee performance and HRM effectiveness, which positively affect organizational performance. These findings offer practical insights for managers and supervisors to improve organizational performance through e-HRM practices.